Association Between Insurance Status at Diagnosis and Overall Survival in Chronic Myeloid Leukemia: A Population-Based Study - Perry, Ashley M. (Cancer, 2017)
BACKGROUND: Chronic myeloid leukemia (CML) can be treated effectively with tyrosine kinase inhibitor (TKI) therapy directed at BCR-ABL, but access to care, medication cost, and adherence may be barriers to treatment. We sought to determine whether insurance status at diagnosis influences CML patient outcomes. METHODS: We used the Surveillance, Epidemiology, and End Results Program (SEER) database and identified 5784 patients age 15 or older, diagnosed with CML between 2007 and 2012, with insurance status documented at diagnosis. Primary outcomes were 5-year overall survival. Covariates of interest included age at diagnosis, race, ethnicity, sex, county-level socioeconomic status, and marital status. Overall survival was evaluated by log-rank test and Kaplan-Meier estimates. RESULTS: Among patients age 15 to 64, insurance status was associated with overall survival (p<0.001), where being uninsured or having Medicaid was associated with worse 5-year OS compared to insured patients (uninsured 72.7%, Medicaid 73.1%, insured 86.6%). For patients over age 65, insurance had less of an impact on OS (p=0.07), with similar 5-year OS rates between patients with Medicaid and those with other insurance (40.2% vs. 43.4%). In multivariable analysis of patients age 15-64, both uninsured (HR 1.93, p<0.001) and Medicaid patients (HR 1.83, p<0.001) had an increased hazard of death compared to insured patients; age under 40, female sex, and married persons also had a lower hazard of death. CONCLUSION: Our findings suggest that CML patients under age 65 who are uninsured or have Medicaid have significantly worse survival compared to patients with other insurance coverage.